2020
DOI: 10.3390/ijerph17041139
|View full text |Cite
|
Sign up to set email alerts
|

When Fathers Begin to Falter: A Comprehensive Review on Paternal Perinatal Depression

Abstract: C.M.); zoccali@unime.it (R.A.Z.); mmuscatello@unime.it (M.R.A.M.)Abstract: The transition to parenthood is considered to be a major life transition that can increase the vulnerability to parental depressive disorders, including paternal perinatal depression (PPND).Although it is known that many fathers experience anxiety and depression during the perinatal period, PPND is a recent diagnostic entity and there are not enough published studies on it. Accordingly, its prevalence and epidemiology are still not well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 86 publications
2
48
0
6
Order By: Relevance
“…Two recent metanalyses showed a PPND prevalence in the word ranging from 10.4% (Paulson and Bazemore, 2010 ) to 8.4% (Cameron et al, 2016 ) and longitudinal studies found that pregnancy is the most sensitive period for the onset of symptoms in both men and women (Madsen and Juhl, 2007 ; Figueiredo and Conde, 2011 ). Therefore, the term Paternal Perinatal Depression (PPND) is gradually replacing Paternal Post-partum/Post-natal Depression (PPD) , to consider and identify the possible onset of depressive symptoms in fathers since the prenatal period (Baldoni, 2010 ; Cameron et al, 2016 ; Bruno et al, 2020 ). Although these terms are commonly used in research, these diagnoses are not even mentioned in the current DSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent metanalyses showed a PPND prevalence in the word ranging from 10.4% (Paulson and Bazemore, 2010 ) to 8.4% (Cameron et al, 2016 ) and longitudinal studies found that pregnancy is the most sensitive period for the onset of symptoms in both men and women (Madsen and Juhl, 2007 ; Figueiredo and Conde, 2011 ). Therefore, the term Paternal Perinatal Depression (PPND) is gradually replacing Paternal Post-partum/Post-natal Depression (PPD) , to consider and identify the possible onset of depressive symptoms in fathers since the prenatal period (Baldoni, 2010 ; Cameron et al, 2016 ; Bruno et al, 2020 ). Although these terms are commonly used in research, these diagnoses are not even mentioned in the current DSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results showed that psychologically distressed men reported higher perceived stress than the men at risk of externalized behavioral problems. According to previous studies, high perceived stress is associated to paternal affective disorders, especially with depressive and anxious symptomatology [ 3 , 26 , 27 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although being a father for most men is a joyful and fulfilling journey [ 1 ], the transition to parenthood, or the arrival of an additional child, can also be perceived as overwhelming and demanding [ 2 ]. Indeed, it has been widely recognized that adjustment to fatherhood may negatively affect the men’s mental health, increasing psychological distress, depression, and anxiety from the prenatal period [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The perinatal period is a time when fathers (like mothers) are at increased risk of depression. [17][18][19] Factors associated with paternal perinatal depression include a personal history of depression, poor social support, receiving insufficient information about pregnancy and having negative perceptions about fatherhood. 20,21 Compared with mothers, fathers are less likely to actively seek professional help when perinatal depression occurs.…”
mentioning
confidence: 99%